Polyoxometalate Li3PW12O40 and Li3PMo12O40 Electrolytes for High‐energy All‐solid‐state Lithium Batteries - Guan, De‐Hui; Wang, Xiao‐Xue; Song, Li‐Na; Miao, Cheng‐Lin; Li, Jian‐You; Yuan, Xin‐Yuan; Ma, Xin‐Yue; Xu, Ji‐Jing (Angewandte Chemie International Edition, 2024)
Solid‐state lithium (Li) batteries promise both high energy density and safety while existing solid‐state electrolytes (SSEs) fail to satisfy the rigorous requirements of battery operations. Herein, novel polyoxometalate SSEs, Li3PW12O40 and Li3PMo12O40, are synthesized, which exhibit excellent interfacial compatibility with electrodes and chemical stability, overcoming the limitations of conventional SSEs. A high ionic conductivity of 0.89 mS cm−1 and a low activation energy of 0.23 eV are obtained due to the optimized three‐dimensional Li+ migration network of Li3PW12O40. Li3PW12O40 exhibits a wide window of electrochemical stability that can both accommodate the Li anode and high‐voltage cathodes. As a result, all‐solid‐state Li metal batteries fabricated with Li/Li3PW12O40/LiNi0.5Co0.2Mn0.3O2 display a stable cycling up to 100 cycles with a cutoff voltage of 4.35 V and an areal capacity of more than 4 mAh cm−2, as well as a cost‐competitive SSEs price of $5.68 kg−1. Moreover, Li3PMo12O40 homologous to Li3PW12O40 was obtained via isomorphous substitution, which formed a low‐resistance interface with Li3PW12O40. Applications of Li3PW12O40 and Li3PMo12O40 in Li‐air batteries further demonstrate that long cycle life (650 cycles) can be achieved. This strategy provides a facile, low‐cost strategy to construct efficient and scalable solid polyoxometalate electrolytes for high‐energy solid‐state Li metal batteries. Polyoxometalates are proposed as a groundbreaking platform for high‐energy all‐solid‐state lithium‐metal batteries. Benefiting from rational structure design, Li3PW12O4o electrolytes exhibit remarkable cost‐effectiveness ($5.68 kg−1), electrochemical stability, and high ionic conductivity (0.89 mS cm−1). The lithium‐metal batteries utilizing sustainable electrolyte achieve more than 200 cycles and the lithium‐air batteries operate over 600 cycles.